2022
DOI: 10.1186/s12890-022-02156-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of adropin as a preliminary test to exclude acute pulmonary embolism: a prospective study

Abstract: Background This study aims to investigate the diagnostic accuracy of adropin as a biomarker to exclude the diagnosis of acute pulmonary embolism (PE). Methods Patients admitted to the emergency department of a tertiary health centre between August 2019 and August 2020 and diagnosed with PE were included in this prospective cohort study. The amount of serum adropin was determined in patients with (PE) and compared with that of healthy volunteers. Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…One of the publications was on adropin levels in patients with acute pulmonary thromboembolism, while the other study was planned in patients with metabolic syndrome. 61 , 62 In a study examining the usefulness of serum transforming growth factor-beta 1 (TGF-beta 1) and connective tissue growth factor (CTGF) levels in predicting disease severity in COVID-19 patients with lung involvement, it was concluded that TGF-beta 1 and CTGF are potential biomarkers that can distinguish COVID-19 patients with lung involvement and indicate disease severity. 63 …”
mentioning
confidence: 99%
“…One of the publications was on adropin levels in patients with acute pulmonary thromboembolism, while the other study was planned in patients with metabolic syndrome. 61 , 62 In a study examining the usefulness of serum transforming growth factor-beta 1 (TGF-beta 1) and connective tissue growth factor (CTGF) levels in predicting disease severity in COVID-19 patients with lung involvement, it was concluded that TGF-beta 1 and CTGF are potential biomarkers that can distinguish COVID-19 patients with lung involvement and indicate disease severity. 63 …”
mentioning
confidence: 99%